Una tumba femenina con ajuar de la Villa Romana de Almenara de Adaja (Valladolid) (2011)
ABSTRACT: Recent works in an area placed North from the pars urbana of the late imperial roman villa at Almenara de Adaja (Valladolid, Spain) have uncovered a female burial with grave goods. These finds suggest the likely situation of a necropolis corresponding to the villa lifetime period. We study the artifacts found in the burial. Results of an analysis on the content of a ceramic vessel found there are also given. This finding complements the available data on the distribution and organization of contemporary habitat and adds up to the known information on cemeteries dating from this time period in the Spanish north inner plateau.